Postdischarge pain, fatigue severity and quality of life in COVID-19 survivors - Demirhan, Esma; Atar, Sevgi; Er, Günay; Okutan, İpek and Kuru, Ömer (The European Research Journal, 2023)
Objectives: Fatigue and pain symptoms were common complaints among post-COVID-19 patients, and these lead to impaired quality of life (QoL). We aimed to evaluate severity of pain and fatigue 3 months after disease onset in discharged COVID-19 patients. Methods: Patients were contacted by phone at their third month following disease onset. Demographic data of the patients such as weight, height, body mass index (BMI), gender, smoking history, comorbidities, length of hospitalization, duration of stay in the intensive care unit, were recorded. The patients’ pain and fatigue severities were evaluated by visual analog scale (VAS). QoL was questioned with the EuroQol Group Association five-domain, three-level questionnaire (EQ-5D-3L). Results: A total of 392 participants enrolled into the study. At admission, 94.6% of the participants had fatigue and 73.7% of them had pain. A high proportion of them still reported fatigue (55.1%) and pain (41.3%) at third month. The mean value of pain-VAS score was 5.37 ± 3.85, and it was 7.58 ± 2.82 for fatigue-VAS at admission. VAS scores of pain and fatigue at third month were 1.44 ± 2.11 and 2.04 ± 2.40 respectively. While 66.6% of the patients reported moderate-severe pain at disease onset, the rate was 18.1% at the third month. And also almost half had severe pain at admission (48%), it was 2.8% at third month. At disease onset 89.6% of the patients reported moderate-severe fatigue (severe: 48%). Aproximately one third of them had moderate-severe fatigue (27.9%) at third month (severe: 5.1%). The mean value of EQ-VAS score was 26.76 ± 20.26 at admission, and it was 78.84 ±16.15 at third month. Statistically significant differences were recorded between the disease onset and third month in terms of pain-VAS fatigue-VAS, and EQ-VAS scores (p < 0.001). Female gender, ICU admission, long duration of hospitalization, older age, higher BMI scores, multiple comorbidities, fatigue and pain severity were related to the decrease in QoL scores. Conclusions: Hospitalized COVID-19 survivors need ongoing support for pain, fatigue complaints and impaired QoL after discharge. The factors that cause poor QoL should be taken into account during post-COVID-19 follow up.